Positive Discipline: Behavioral Management Skills for Parents and Teachers Part 3—Fostering the Parent–Child and Teacher–Student Relationship to Build Responsibility - Victor Harris; Whitney Fung; Sarah Ellis; Alison Schmeer (EDIS)
Tell me and I forget, Teach me and I may remember, Involve me and I learn.